Implementation of Autonomous Maintenance in Total Productive Maintenance - Atikha Sidhi Cahyana; Juli Guritno (Universitas Muhammadiyah Sidoarjo, 2021)
The purpose of this research is to increase the Avaibility rate, Performance rate and OEE value on pipe extruder line 9 at PT. Wahana Tunas Utama Rucika which is engaged in manufacturing PVC pipe products (Poly Vinyl Clhoride). In order to increase productivity, Total Productive Maintenance (TPM) is measured by calculating OEE. The method used in solving this problem the 8 pillars of TPM with the Autonomous Maintenance (AM) method. The implementation of the TPM pillar aims to increase the knowledge, responsibility and skills of production operators related to machines, so that overall productivity will increase. AM uses a structured and documented system so that this program can run consistently. The results of the implementation of the proposed improvements showed that the Availability rate had to increase by 3.61%, the Performance rate had to increase by 3.41% and OEE had to increase by 3.25% after the proposed improvements 6 months.